Principled bundle block adjustment with multi-head cameras - Eleonora Maset; Luca Magri; Andrea Fusiello (ISPRS Open Journal of Photogrammetry and Remote Sensing, 2024)
This paper examines the effects of implementing relative orientation constraints on bundle adjustment, as well as provides a full derivation of the Jacobian matrix for such an adjustment, that can be used to facilitate other implementations of bundle adjustment with constrained cameras. We present empirical evidence demonstrating improved accuracy and reduced computational load when these constraints are imposed.